A prospective study of clinico-radiological assesment and management of obstructive jaundice in Mmimsr, Mullana - Wilku, Karaninder Singh; Gandhi, Himank (International Surgery Journal, 2021)
Background: Obstructive jaundice poses diagnostic and therapeutic challenges. This study was undertaken to highlight the clinical and radiological assessment of obstructive jaundice in our setting and to approach for early diagnosis and treatment before irreversible tissue insult sets in. Methods: Present study was prospective study conducted at Maharishi Markandeshwar Institute of Medical Sciences and Research, Mullana, Ambala. Data were collected on prescribed proforma and analyzed stastically. Results: A total of 50 patients were studied. It is more common in productive adult with the mean age of 51.04±12.40 years. The male to female ratio was 1:1.08. Majority of the patients were having benign pathology (62%) and choledocholithiasis was the commonest benign cause. Abdominal ultrasound was the diagnostic imaging done in all patients and revealed dilated CBD (>1 cm) in 78% cases, dilated IHBR in 96%of cases and multiple CBD stones in 78.3% of cases. CT was reserved for suspected malignant and MRCP was planned in stone or benign causes. 70% patients were selected for ERCP and 62% of patients underwent definitive open procedure viz choledocholithotomy (40%), hepaticojejunostomy (12%). Conclusions: Obstructive jaundice in our study was more prevalent in females and the cause is mostly CBD stones. The result suggests that early diagnosis and treatment plays vital role in the prognosis of patients with obstructive jaundice.